2015
DOI: 10.1016/j.comgeo.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Bichromatic compatible matchings

Abstract: For a set R of n red points and a set B of n blue points, a BR-matching is a non-crossing geometric perfect matching where each segment has one endpoint in B and one in R. Two BR-matchings are compatible if their union is also non-crossing. We prove that, for any two distinct BR-matchings M and M , there exists a sequence of BR-matchings M = M 1 , . . . , M k = M such that M i−1 is compatible with M i . This implies the connectivity of the compatible bichromatic matching graph containing one node for each BR-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Considering the notion of compatibility, most of the work has been done in the straight-line setting, e.g., in the context of perfect matchings with [5,7] or without [1,2] vertex coloring, or for edge-disjoint compatibility [3,11]. Aichholzer et al [4] showed, in the straight-line setting, that the compatibility graph of plane spanning trees is connected with diameter O(log k), where k denotes the number of convex layers of the point set.…”
Section: Related Workmentioning
confidence: 99%
“…Considering the notion of compatibility, most of the work has been done in the straight-line setting, e.g., in the context of perfect matchings with [5,7] or without [1,2] vertex coloring, or for edge-disjoint compatibility [3,11]. Aichholzer et al [4] showed, in the straight-line setting, that the compatibility graph of plane spanning trees is connected with diameter O(log k), where k denotes the number of convex layers of the point set.…”
Section: Related Workmentioning
confidence: 99%
“…[3] proved that such a sequence of at most O(log n) steps always exists. Questions of whether any matching of a given point set can be transformed into any other and how many steps it takes (that is, the connectivity of and the distance in the so-called reconfiguration graph of matchings, as well as its other properties) have been investigated also for matchings on bicolored point sets and for edge-disjoint compatible matchings, see for example [5,8,19]. Our results.…”
Section: Introductionmentioning
confidence: 97%

On Compatible Matchings

Aichholzer,
Arroyo,
Masárová
et al. 2021
Preprint
“…Flips in triangulations are an instance of a more general question: Given a class of spanning graphs G of a point set S, which local operations can transform one element of G into another? Several operators have been introduced for different classes of spanning graphs that are not triangulations, such as perfect matchings, plane Hamiltonian cycles and plane spanning trees [6,9,36]. One class of graphs that has received much attention in these type of operators, is the set of plane spanning trees of a point set.…”
Section: Convex Shape Delaunay Graphs and Treesmentioning
confidence: 99%